Magnetite nanoparticles from waste mill scale as a nanoadsorbent for copper metal removal in aqueous solutions - Sulaiman, Syazana (2021)
Heavy metal pollution has become one of the main concerns in the environment owing to continuous growth in the global population, industrial activities, and development. The ability and the potential of magnetite nanoparticles (MNP) from waste mill scales as low-cost metal adsorbents were examined for the adsorptive removal of copper (Cu) ions from an aqueous solution. The adsorption technique and inexpensive adsorbent were used as a fascinating alternative for the removal of Copper from wastewater. The purpose of this work was to develop an adsorbent by using waste mill scale product for the adsorption of copper ions, owing to its abundance of waste product worldwide, and could serve as an alternative for a low-cost absorbent. The waste mill scales were synthesized via high energy ball milling (HEBM) to obtain magnetite nanoparticles (MNP). The resultant MNP were analysed utilising X-ray Diffraction (XRD), Vibrating Sample Magnetometer (VSM), Transmission Electron Microscopy (TEM), Brunauer-Emmett-Teller (BET), Fourier Transform Infrared Spectroscopy (FTIR), Zeta Potential and Field Emission Scanning Electron Microscopy with Energy Dispersive X-Ray Spectroscopy (FESEM-EDX). The sorption characteristics were studied together with kinetic and isotherm equilibrium studies. Also, the adsorption studies were performed to investigate the influence of significant parameters including contact time, starting concentrations, pH, temperature, and adsorbent dosage. It was noticed that the MNP adsorption kinetics study was best fitted by the Pseudo-second-order kinetic model with superior correlation coefficients (R2 ) of 0.999. Batch studies indicated that about 63.6% of copper ions were removed in the first 30 mins of the adsorption test at optimum pH 5.4 at a temperature of 26 °C. The isotherm experimental data were examined using Langmuir, Freundlich and Temkin model. The adsorption behaviour of copper ions was fitted with Temkin isotherm model and the highest adsorption capacities, qmax was 4.408 mg/g. The highest adsorption capacity, qe of 4.408 mg/g with removal efficacy (%RE) of 63.6% was attained at the best treatment condition of pH 5.4, adsorbent dosage of 0.05 g and 240 minutes of contact time. The MNP reusability and regeneration efficiency of 70.23% was achieved after three cycles, thereby indicating its suitability as a promising low-cost adsorbent for copper for industrial application and good remediation performance. This study suggests the use of MNP obtained from the waste mill scales are affordable adsorbent for the adsorptive removal of other heavy metals from water.